Knowledge, attitude, and practice (KAP) questionnaire on melioidosis: development and validation and associated factors among field agricultural farmers in Kelantan, Malaysia - Abdullah, Nor Azlina (2024)
Background: Melioidosis, caused by the bacterium Burkholderia pseudomallei, is a significant public health concern in Malaysia, particularly among field agricultural farmers who face a heightened risk of exposure due to their occupational activities. Despite its importance, there is a lack of validated questionnaires to assess the knowledge, attitude, and practices (KAP) regarding melioidosis and study its associated factors among this high-risk population. Objectives: This study aimed to develop and validate a new questionnaire assessing KAP towards melioidosis among fields agricultural farmers in Kelantan, Malaysia. Additionally, it was aimed to determine the KAP scores and associated factors among them. Methods: This two-phase study was conducted between May 2023 and March 2024. In Phase 1, a KAP questionnaire was developed and validated through rigorous processes involving literature review, content validation, face validation, item response theory (IRT), exploratory factor analysis (EFA), and confirmatory factor analysis (CFA). The questionnaire was administered to 432 field agricultural farmers in Kelantan (222 for EFA, 210 for CFA). In Phase 2, a cross-sectional study was conducted among 392 farmers to assess their KAP scores and identify associated factors using the validated questionnaire. In the first phase, data were analysed usinR software, while in the second phase, the analysis was conducted using SPSS version 26. Results: The proposed melioidosis KAP questionnaire named M-KAP, which consisted of 62 items has demonstrated excellent content validity (S-CVI/Ave: 0.97 for knowledge, 0.96 for attitude, 0.99 for practice) and face validity (S-FVI/Ave: 0.99 for knowledge, 0.95 for attitude, 1.0 for practice). IRT, EFA and CFA confirmed the construct validity and reliability of the questionnaire with analysis revealed an acceptable range of difficulty and discrimination in IRT, reliable internal consistency with Cronbach's alpha values of 0.7 and above in EFA, and satisfactory composite reliability, as indicated by Raykov's rho values exceeding 0.70 in CFA. In Phase 2, the total mean percentage for knowledge, attitude and practice were 36.4%, 62.6% and 77.6% respectively. Factors significantly associated with higher knowledge scores were female gender (adjusted β= 3.84, p=0.013), and individuals with affected close contacts (adjusted β= 7.20, p=0.008). However, those working with non-paddy crops (adjusted β= -6.17, p<0.001) associated with lower knowledge of melioidosis. Smoker associated with lower attitude (adjusted β= -1.69, p=0.008) and non-paddy crop workers (adjusted β= 1.67, p=0.007) associated high higher attitude score. Higher education level (adjusted β= -1.56, p=0.011) and having multiple job scopes (adjusted β= -1.58, p<0.001), were associated with lower practice scores.